2011
DOI: 10.1007/s00127-011-0404-6
|View full text |Cite
|
Sign up to set email alerts
|

The effect of rural-to-urban migration on social capital and common mental disorders: PERU MIGRANT study

Abstract: ObjectiveThis study aims to investigate whether there are differences in the prevalence of common mental disorders and social capital between migrant and non-migrant groups in Peru.MethodologyThe PERU MIGRANT study is a cross-sectional study comprising three groups: an urban group from a shanty town in Lima; a rural group from a community in Ayacucho-Peru; and a migrant group originally from Ayacucho currently living in the same urban shanty town. Common mental disorders were assessed using the General Health … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
24
1
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 28 publications
(46 reference statements)
4
24
1
1
Order By: Relevance
“…Li et al [25] found that MWs’ mental health was significantly worse than rural dwellers. Our findings are only partly consistent with these Chinese studies but very similar to a Swedish immigrant study [43] and a Peru rural-to-urban migrant survey; [9] both found significant differences in common mental illness between migrants and native controls disappeared after the adjustment for their unmatched socio-economic factors, and Tonghog et al [43] concluded that the association between immigrant status and mental illness appeared to be a primary effect of a higher prevalence of social and economic disadvantage among immigrants in Sweden.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Li et al [25] found that MWs’ mental health was significantly worse than rural dwellers. Our findings are only partly consistent with these Chinese studies but very similar to a Swedish immigrant study [43] and a Peru rural-to-urban migrant survey; [9] both found significant differences in common mental illness between migrants and native controls disappeared after the adjustment for their unmatched socio-economic factors, and Tonghog et al [43] concluded that the association between immigrant status and mental illness appeared to be a primary effect of a higher prevalence of social and economic disadvantage among immigrants in Sweden.…”
Section: Discussionsupporting
confidence: 91%
“…Our findings that, migrant status had no association with poor psycho-QOL and a significant association with lowered risk of depression were in line with a Peru migrant survey [9] but discordant with Swinnen's meta-analysis. This discordance may be due to the difference between psycho-QOL and depressive symptoms, with the former being a more comprehensive mental health indicator.…”
Section: Discussionsupporting
confidence: 86%
“…The cognitive component evaluates the following: trust in the community, interpersonal relationships among community members, sense of belonging to the community, and perception that other community members may try to take advantage of oneself if they had the chance. The score on the structural component was categorized into quartiles and subsequently dichotomized into high (second, third, and fourth quartiles) and low (first quartile) structural social capital, as previously reported in a study on social capital and mental health in Peru (Loret de Mola et al, 2012). The score on the cognitive component was categorized into low (1–2 points) and high (3–4 points) cognitive social capital, as recommended by De Silva et al (De Silva et al, 2006).…”
Section: Methodsmentioning
confidence: 99%
“…The population has grown consistently because of internal migration in Peru from rural to urban areas in recent decades. 15 This migration principally of the Andean Participants. Potential participants were identified using the information from a census performed in the year 2000 by a local non-governmental organization Asociacion Benefica Proyectos en Informatica, Salud, Medicina, y Agricultura (AB PRISMA), from which an age-stratified sample was drawn (three age strata were considered: 5-14, 15-24, and 25 years of age).…”
Section: Methodsmentioning
confidence: 99%